2013
DOI: 10.1155/2013/469076
|View full text |Cite
|
Sign up to set email alerts
|

A PEFKS- and CP-ABE-Based Distributed Security Scheme in Interest-Centric Opportunistic Networks

Abstract: Security is a crucial issue in distributed applications of multihop wireless opportunistic network due to the features of exposed on the fly communication, relaxed end-to-end connectivity, and vague destinations literately. In this paper, we focus on problems of user privacy leakage and end-to-end confidentiality invasion in content-based or interest-centric wireless opportunistic network. And we propose a public-encryption-with-fuzzy-keyword-search- (PEFKS-) and ciphertext-policy-attribute-based-encryption- (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, the computation burden of the scheduling is shared to all the active nodes. Aiming to optimize the tradeoff between the tracking accuracy and the energy cost for collaborative target tracking in WSNs, a dynamic sensor selection scheme based on genetic algorithms was proposed in [23].…”
Section: Related Workmentioning
confidence: 99%
“…However, the computation burden of the scheduling is shared to all the active nodes. Aiming to optimize the tradeoff between the tracking accuracy and the energy cost for collaborative target tracking in WSNs, a dynamic sensor selection scheme based on genetic algorithms was proposed in [23].…”
Section: Related Workmentioning
confidence: 99%
“…One way to address the critical issues in maintaining the strength of the structure and ensuring the safety of engineers is to apply appropriate pretightening force to the bolted joints and conduct long-term online monitoring of their axial stress. The most frequently used nondestructive estimation methods of stress include the photoelasticity method [1], resistance strain gauge method [2], piezoresistance method [3], active sensing method [4,5], and ultrasonic testing method [6][7][8][9]. Among all these methods, the ultrasonic testing method is considered as a potential alternative technique due to its convenience to measure bolt tension with better accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…It is common that bolts loosen over a period of time, and this phenomenon may cause the out-of-plane rotation of tall shear walls. Song et al [40][41][42][43] monitored the phenomenon of bolts looseness and found it common in the structures with bolted connection. In summary, the present PC shear wall with dry connection cannot achieve the same seismic performance as the RC shear wall.…”
Section: Introductionmentioning
confidence: 99%